Multiwave laser source for simultaneous sounding ozone and critically related to ozone chemicals - Baschenko, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The scheme of multiwave laser source, suitable for simultaneous probing ozone and chemicals critically related to ozone (such as HCl, ClONO₂, N₂O₅, HNO₃) participating in its formation and destruction, when using differential absorption with scattering method (DIAS) for sounding, is suggested. Such a source may consist of excimer laser complex complemented with a converter implementing Stimulated Raman Scattering phenomena. Both complex and converter are assembled and operate using “oscillator-amplifier” optical scheme, which provides simultaneous generation at few wavelengths in a wide spectral range due to discrete Raman conversion with its fine tuning due to complex implementation. Experimental pattern of 3-waves laser source elaborated with this scheme is described. In our attempt laser source consists of XeCl*-excimer laser complex supplemented with SRS-converter with dense hydrogen. Possibilities of simultaneous generation at three lines - 308, 353 nm and one of the wide set: 414, 499, 635 or 855 nm – with fine tuning of all lines within up to 1 nm are demonstrated. The advantages of offered scheme and difficulties in its realization are discussed.